SDGs as a Theme for Practice in Digital Circuits: experience report - Stringhini, Denise; Tosta, Thaína Aparecida Azevedo; Oliveira, Tiago de (International Journal of Computer Architecture Education, 2023)
This paper reports on the experience of using the SDGs - Sustainable Development Goals of the UN 2030 Agenda - as a theme for the practice of the Digital Circuits course at the Institute of Science and Technology of the Federal University of São Paulo (ICT-Unifesp). The course is part of the curricularization of university extension and the implementation of new guidelines for Engineering courses. The experience described here was proposed during the reformulation of the pedagogical project of the Computer Engineering course. This work shows the preliminary results of this implementation through an experience report in two Digital Circuits classes in the first semester of 2023. Following a project-based learning approach, students proposed digital circuit projects with SDG themes. Based on some proposed technical prerequisites, students were encouraged to understand the SDGs from a global problems perspective, conduct local field research to identify these problems in their communities, and propose solutions in their projects. As preliminary results, we present a selection of the proposed projects, whose chosen themes indicate the students’ understanding of global issues and their ethical commitment to the communities around them.